A challenge-response mechanism for securing online social networks against social bots. (20th August 2019) - Mohamed, Torky; Ali, Meligy; Hani, Ibrahim
Social bots is fast becoming a serious security threat to online social networks (OSNs). Social bots are automated software tools able to execute malicious activities in OSNs systems in an automated fashion. It can perform auto-sharing and posting, sending fake friend requests, harvesting private information, etc. There is evidence that social bots play a crucial role in penetrating privacy and security of social networks. Hence, these malicious software tools represent a big security challenge against social network service provider (SNSP). In this paper, we introduce a novel antibot mechanism called Necklace CAPTCHA for securing OSNs platforms against the automated behaviours of social bots. Necklace CAPTCHA is an Image-based CAPTCHA, which utilises the functionality of Necklace Graph approach to generate its challenge-response tests in a novel fashion. The results demonstrated that Necklace CAPTCHA is an effective and secure anti-bot mechanism compared with other CAPTCHAs in the literature with respect to the usability and security metrics.